Intergenerational communication & well-being in Aboriginal life - Fox, Terri-Lynn; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Faculty of Arts and Science, 2004, 2004)
218 leaves : ill. 29 cm. This thesis discusses intergenerational communication and well-being in Aboriginal life, using a literature review and research conducted in relation to the Blood people and culture. It addresses issues concerning lack of communication of traditional ways of knowing, teaching, and being. Interviews were used to better understand the dynamics of intergenerational communication and well-being. It is historically know by First Nations communities that the older people of the clan or tribe taught the children from infancy to adolescence. This, unfortunately, is not the case in many First Nations communities today, due to colonization, assimilation, and segregation. It is hoped this research will assist those who wish to develop, implement and enhance future social, educational, and health programs for the well-being of the First Nations child, family and community. The results also suggest ways in which to enhance and foster the value of elders in the community.